Nitrogen use efficiency of pioneer and modern wheat cultivars - Beche, Eduardo; Benin, Giovani; Bornhofen, Elesandro; Dalló, Samuel Cristian; Sassi, Luiz Henrique Scarparo; de Oliveira, Ronaldo (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to characterize Brazilian wheat cultivars, developed in different decades, as to their nitrogen use efficiency, under different availabilities of the nutrient. Ten wheat cultivars, released between 1940 and 2009, were subjected to four nitrogen fertilization rates (0, 60, 120, and 180 kg ha‑1 N), under a controlled environment, in a randomized complete block design, with three replicates. Grain yield increased in 0.54, 0.74, 0.74, and 0.82% per year at the rates of 0, 60, 120, and 180 kg ha‑1 N, respectively. Nitrogen uptake and utilization efficiencies were positively associated with N use efficiency, with strengthening relation under high N availability conditions. Modern cultivars are more efficient in N use and tolerate lower rates of the nutrient in comparison to pioneer cultivars. For the development of more efficient cultivars in N use, wheat‑breeding programs should prioritize the selection of genotypes with higher N uptake, remobilization, and utilization efficiencies.